Perception of /ɡ/ in French: A Comparative Study of Students with and without Experience of Studying Abroad - Kampeera, Wannachai (Journal of Letters, 2019)
Research in Second Language Acquisition (SLA) shows that the Study Abroad context (SA) can improve the four core language skills: reading, writing, listening and speaking. However, the question of how much SA helps improve the perception of individual phonemes, a more specific skill, has not yet been widely addressed. This study investigates Thai students’ perceptual ability with regards to French /ɡ/ in phonetic environments which trigger contextual variations of the phoneme. Two groups of undergraduate Thai learners of French were involved: returnees from Francophone countries (Study Abroad context: SA) and those who had never been to Francophone countries (At Home context: AH). The research instrument is Two Groups Post-Test Comparison, which includes five series of tests spotting the phoneme /ɡ/ preceding different vowels in various syllable structures. The results show no statistically significant difference between the two groups. The findings are likely due to the fact that phonemic perceptual ability is a very specific skill that needs tailored phonetic-phonological training to improve. When considering overall scores, both groups were able to perceive /ɡ/ in unreal words with open syllables. Nevertheless, both groups were shown to be less perceptive of /ɡ/ in real and longer words.